RESOURCE AVAILABILITY AND QUALITY OF EDUCATION IN PRIVATE AND PUBLIC KINDERGARTENS - Matthew Timothy Palit; Cicha Widia, Adellia, Imelda Rosen, Alfinia Tecuari, Ropikha Lidia Silap, Yeremia; Yesyurun Munthe (CV. ADIBA ASIHA AMIRA, 2023)
The availability of resources has an impact on the level of education quality. From the research that has been conducted using the interview method to two private and public kindergartens in Palangka Raya with the subject of teachers and parents of students and librarian references, the results show that the availability of resources such as funds, facilities or facilities and teachers who are competent in their fields has an impact on the quality of education in schools. If these resources are well available, the quality of education in the school is also good. With cooperation through various parties such as parents and related agencies such as health can support the plan with the aim of advancing the quality of education to be even better. The involvement of various parties plays an important role in the plan because then the limited resources can be overcome so that the goal can be achieved.